Principal Leadership on Student Achievement in India - Bijumon Thomas; Osman Abdul Jhariel (Journal of Management Practices, Humanities and Social Sciences, 2019)
The present study has been envisioned to explore how the leadership of the principal influenced students' achievement within the context of schools in India. Studies in developed countries have revealed that the leadership of principals has influenced students' achievement. On the other hand, in India, this type of study is scarce. And the details how the leadership of the principals influenced students' achievements are still unexplored. The present study has used a qualitative case study to better understand the phenomenon. To meet the objective of the study, the researchers have conducted in-depth interviews with school principals and teachers in five different schools in India. Likewise, students' progress report and minutes of meetings of parents, teachers, and school staff were requested for further analysis. The data derived from the data sources were triangulated. The results of the analysis of the transcription of the interviews have offered descriptions of how the leadership of the principal influenced students' achievements. The findings from the interviews with principals were validated by the senior teachers. First, the leadership of the principal influenced students' achievements through the curriculum. In schools, the principals are the ones who decide on the type or form of the curricular, co-curricular and extra-curricular programs that will be brought to students. Second, their leadership clarifies the focus of the delivery of instructions. The principals articulate the goals of teaching and learning in class. Third, the leadership of the principals provides support to teachers and ensures the delivery of quality educational services to the students. In schools where the leadership of the principal is felt the professional development of teachers and the achievements of students were the top priority. Lastly, the leadership of principals encourages parents' school involvement, which helps students to see the value of their achievements in schools.